The role of Life’s Crucial 9 in cardiovascular disease incidence and dynamic transitions to dementia - Yanyu Zhang; Darui Gao; Jie Liang; Mengmeng Ji; Wenya Zhang; Yang Pan; Fanfan Zheng; Wuxiang Xie (Communications Medicine)
Abstract Background Cardiovascular disease (CVD) often coexists with dementia as the contributor to disease burden in the aging population. Although the effects of several modifiable factors on the CVD and dementia risk have been increasingly recognized, their impacts on their dynamic transitions have not yet been explored. Therefore, we aimed to explore the role of Life’s Crucial 9 (LC9; which includes measurements for diet, physical activity, smoking, BMI, cholesterol, blood pressure, blood sugar, sleep, and psychological health) in the dynamic transitions of CVD and dementia. Methods Using the UK Biobank (351,945 CVD-free participants, aged 40–70, and 55.1% female), we applied Cox proportional hazard model and the multi-state model to explore the relationships of LC9 with the dynamic transitions of CVD to dementia. We further examined which component of LC9 (behavior subscale, biological subscale, and psychological health) contributed to these dynamic transitions. Results Of the total CVD-free participants, we find that there are 35,316 newly onset CVD cases and 5426 dementia cases with a maximum follow-up of 16 years. Findings reveal that higher LC9 scores are associated with a lower risk of CVD, dementia, and dynamic transitions from CVD to dementia. Furthermore, these results suggest that psychological health contributes more strongly to dynamic transitions from CVD to dementia than the behavioral or biological subscales (Atrial fibrillation to dementia: hazard ratio [HR] = 1.48, 95% confidence interval [CI] = 1.20–1.81; Ischemic stroke to dementia: HR = 1.39, 95% CI = 1.02–1.89; Myocardial infarction to dementia: HR = 1.48, 95% CI = 1.03–2.13; Heart failure to dementia: HR = 1.59, 95% CI = 1.22–2.07). Conclusions Our findings highlight the need for closer surveillance of psychological health in CVD patients to lower the risk of subsequent dementia incidence.